Addressing Challenges of Biological Animations - Lowe, Richard; Boucheix, J. (Universite Pierre-Mendes-France, 2012)
Much research on learning with animations has used mechanical rather than biological subject matter. Interactions in mechanical systems tend to involve components acting as coherent wholes (i.e., extrinsic changes such as translations). In contrast, when parts of a biological system interact, they can also undergo transformations (intrinsic changes) due to the non-uniform, non-rigid nature of their constituent material. The behaviour of unfamiliar mechanical systems can therefore be much easier to predict than that of unfamiliar biological systems. This theoretical paper argues that learners may have more difficulty in processing animations of biological systems because of their relative dynamic indeterminacy. It suggests that instead of presenting the animated subject matter in its entirety, key aspects could be dealt with incrementally and cumulatively.